2006
DOI: 10.1021/ac052105w
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Synthetic Origin of Methamphetamine Samples by 2H NMR Spectroscopy

Abstract: Samples of methamphetamine, prepared according to the most common synthetic pathways, were submitted to natural-abundance 2H NMR spectroscopy. The deuterium content at the various sites of the molecule was found to depend on its synthetic history. The technique provides a chemical fingerprint of methamphetamine samples and can give hints to trace back the starting materials and the synthetic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 8 publications
(12 reference statements)
1
13
0
Order By: Relevance
“…The inclusion of d 2 H analysis enables us to discriminate ephedrines having similar d 13 C and d 15 N values. In general, hydrogen isotope patterns are obtainable with 2 H NMR or isotope ratio mass spectrometry (IR-MS), and are useful to trace a substance's origin [9][10][11][12][13][14]. The hydrogen isotope patterns in this study were consistent with the site-specific deuterium contents observed with 2 H-NMR in our previous work [9].…”
Section: Resultssupporting
confidence: 86%
“…The inclusion of d 2 H analysis enables us to discriminate ephedrines having similar d 13 C and d 15 N values. In general, hydrogen isotope patterns are obtainable with 2 H NMR or isotope ratio mass spectrometry (IR-MS), and are useful to trace a substance's origin [9][10][11][12][13][14]. The hydrogen isotope patterns in this study were consistent with the site-specific deuterium contents observed with 2 H-NMR in our previous work [9].…”
Section: Resultssupporting
confidence: 86%
“…This has resulted in increased clandestine synthesis and trafficking of the illicit drug [1]. Recent studies have increasingly focused on isotope analysis of methamphetamine and its precursors by isotope ratio mass spectrometry (IRMS) [2][3][4][5][6][7][8] and deuterium nuclear magnetic resonance spectroscopy ( 2 H NMR) [9,10]. It is thought that isotope analysis can provide sample linking information and intelligence information on the source of precursors, especially in cases where traditional forensic drug analysis techniques may fail.…”
Section: Introductionmentioning
confidence: 99%
“…Methamphetamine is commonly synthesized from either (À)-ephedrine/(+)-pseudoephedrine [5,8,[11][12][13][14][15][16][17][18][19][20] or phenyl-2-propanone [9,11,14,21]. Synthesis from either of the ephedrine-type precursors is most common in New Zealand and in the South East Asia region.…”
Section: Introductionmentioning
confidence: 99%
“…Some articles have introduced the analytical methodologies for separating enantiomers of amphetamine-type substances (ATS), including high-performance liquid chromatography (HPLC), 5,7,8 capillary electrophoresis (CE), [9][10][11][12][13][14] gas chromatography-mass spectrometer (GC-MS), [15][16][17] ultra performance liquid chromatography-mass spectrometer (UPLC-MS), 18,19 capillary electrophoresismass spectrometry (CE-MS) 3,20-23 and nuclear magnetic resonance (NMR) spectroscopy. 24,25 Nuclear magnetic resonance spectroscopy can provide chiral information of enantiomers by adding the chiral solvating agent before detecting, while it usually needs to combine other methods (such as GC-MS) to identify an unknown seized mixture. 26 For both GC and HPLC techniques, a prederivatization step or a specific chiral column is necessary for successful separation.…”
Section: Introductionmentioning
confidence: 99%